DIALECTIC INTERACTION OF QUANTITY, QUALITY AND RELATION IN SIMILE DOMAIN - Oleniak, Mariana (Advanced Education, 2019)
This paper attempts to shed some light on the problem of correlation of such ontological categories as quality, quantity and relation in similes. The matter in question is significant since it relates to the problem of anthropocentrism in language. It shows the speaker’s attitude to the information encoded in a simile by consciously choosing a vehicle via measuring a tenor’s salient feature against an implied abstract scale of objects, notions, phenomena, etc. that possess a particular quality to a certain extent. The nature of the ground of simile is described to be gradable, capable of being subjectively measured from the perspective of the speaker’s environmental perception. The gradability of a shared feature shown as a scale of potential vehicles lends itself to the interpretation as a fragment of the linguistic worldview displaying a range of scale markers typical of a certain linguistic community in a certain historical period of time. The polar opposite notions on an implied scale are depicted to represent a (proto/stereo) type and an anti-(proto/stereo)type typical of certain linguo-cultural domains in a particular fragment of a linguistic worldview. By moving from the explanatory examples to the analysis of empirical material the author concludes that the categories of quantity, quality and relation are intrinsic in every simile and manifest themselves in the choice of a tenor-vehicle pair that do not exist within simile other than in relation to each-other. The material described in the article serves as an evidence of language dependence on historical and social parameters. The paper explains the mechanism of creation of the congruous and ironic similes according to the universal process of simile formation where the unity of quantity, quality and relation are the key factors of its existence.